Impact of gender on the willingness to participate in clinical trials and undergo related procedures in individuals from an Alzheimer’s prevention research cohort - Lidia Canals-Gispert; Alba Cañas-Martínez; Gema Huesa; Marc Suárez-Calvet Alomà; Marta Milà-Alomà; Eider Arenaza-Urquijo; Davide Cirillo; Annemarie Schumacher Dimech; Maria Florencia Iulita; Julie Novakova Martinkova; Maria Carmela Tartaglia; Frances-Catherine Quevenco; et al. (Alzheimer’s Research & Therapy)
Abstract Background Although there is growing evidence of the association between gender and early diagnosis of preclinical Alzheimer's disease, little attention has been given to the enrolment ratio of men and women in clinical trials and data reporting. Methods This study aims to analyze gender differences in sociodemographic factors associated with the willingness to participate in clinical trials and undergo specific procedures in the context of an Alzheimer's disease prevention research cohort. 2544 cognitively unimpaired participants from the ALFA parent cohort (age 45–75 years) of the Barcelonaβeta Brain Research Center were contacted through a structured phone call to determine their willingness to participate in Alzheimer's disease clinical trials and undergo trial-related procedures (magnetic resonance imaging, lumbar puncture, positron emission tomography, and cognitive assessment). Sociodemographic data on education, occupational attainment, civil and caregiver status were gathered. Stepwise logistic regression models were performed in order to study the interaction between gender and sociodemographic factors in the willingness to participate in clinical trials and to undergo clinical trial-related procedures. Results 1,606 out of the 2,544 participants were women (63.1%). Women were significantly younger and had lower educational attainment compared with men. In addition, women were more likely to be caregivers, single and unemployed. Women showed a significantly lower willingness than men to participate in a clinical trial (p = 0.003) and to undergo a lumbar puncture (p < 0.001). Single women were less willing to participate in clinical trials than single men (p = 0.041). Regarding clinical trial-related procedures, women with higher years of education were significantly less willing to undergo a lumbar puncture (p = 0.031). Conclusion We found gender differences regarding the sociodemographic factors that predict the willingness to participate in clinical trials and to undergo clinical trial-related procedures. Our results highlight the urgent need to design recruitment strategies accounting for gender-related factors, particularly those related to marital status and education.